Chitosan–Lactic Acid Mouthwash Enriched with Eucalyptus Grandis Oil: Formulation and Antimicrobial Properties (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Oral health needed improvement through additional mechanical methods, particularly the use of mouthwash formulated with natural ingredients such as chitosan and Eucalyptus grandis. This study aimed to evaluate the physical stability and antimicrobial activity of mouthwash formulations and to identify the most optimal formula among the combinations. Chitosan was characterized using Fourier Transform Infrared Spectroscopy (FT-IR), while Eucalyptus grandis was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). All mouthwash formulations met standard requirements in terms of organoleptic properties, pH levels, and viscosity, indicating good physical stability. The antimicrobial activity was tested against Streptococcus mutans, Staphylococcus aureus, and Candida albicans. The results demonstrated that all formulas exhibited moderate to strong antimicrobial activity. Among the five tested formulas, formula V was found to be the most effective. It showed an average inhibition zone diameter of 11.5 ± 1.94 mm for Streptococcus mutans, 13 ± 1.9 mm for Staphylococcus aureus, and 13.7 ± 0.72 mm for Candida albicans. These findings indicated that formula V had the best combination of physical stability and antimicrobial performance, making it the most optimal formulation.